Maternal mental health during COVID-19 pandemic outbreak: A cross-sectional comparative study - Alenezi, Shuliweeh; Abdulghani, Sahar H.; Shaiba, Lana A.; Hadid, Adnan; Al Ohaly, Rana Y.; Aldeghaither, Basmah S.; Alessa, Rania A.; Alyahya, Ahmed S. (Frontiers in Public Health, 2023)
Background As COVID-19 spread in several countries, social distancing measures was implemented around the world, affecting the quality of lives for millions of people. The impact was more pronounced on vulnerable populations such as pregnant women, who are at even more risk due to their suppressed immune system. Moreover, mental health disorders are more common among pregnant women compared to non-pregnant. This study aims to assess the influence of social isolation measures due to the COVID-19 pandemic on the mental health of women in their third trimester and postpartum. Material and methods This is a cross-sectional survey-based study conducted in Khalid University Hospital, Riyadh, Saudi Arabia, between the months of April to May 2021, to explore depression and anxiety levels in females who gave birth during the COVID-19 pandemic. In addition to background demographic data, the survey included Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder Scale-7 (GAD-7) were utilized to detect symptoms of depression and anxiety, respectively. Results A total of 283 women were included in this study, almost half of them were ante-natal (n-141) and the rest were post-natal (n = 124). 62.3% were in the age groups of 25–35 years. Based on the PHQ-9 scoring, 65% of the study sample had depression (ranging from mild to severe). Moreover, based on GAD-7 scoring, 49.1% had anxiety (ranging from mild to severe). No association was found between PHQ-9 and GAD-7 scores and different sociodemographic and obstetric factors. Additionally, the mean scores of women infected with COVID-19 vs. women who has never been diagnosed with COVID-19 were closely comparable. Conclusions We reported a high prevalence of depression and anxiety among pregnant women during COVID-19 pandemic. Policymakers and health care providers are advised to implement targeted preventive measures for pregnant women to improve mental health in times of epidemics.